Letter from Svante Arrhenius to Georg Bredig, March 1912 - Arrhenius, Svante (1912)
Svante Arrhenius (1859-1927) writes to Georg Bredig (1868-1944) to congratulate him on his new laboratory. He additionally discusses the scientific work of other chemists.
Keywords: Arrhenius, Svante, 1859-1927; Bredig, Georg, 1868-1944; Nobel Prize winners; Nobel Prizes; Chemistry